The Role of 16-Detector Computed Tomography in the Detection of Coronary Artery Origination Anomalies - Elmali, M.; Bilgici, M.; Gülel, O.; Bayrak, I.K.; Aslan, Selcuk; Çelenk, Ç. (My University, 2006)
Coronary artery origination anomalies are detected during catheter angiography and can rarely be a cause of patient's complaint. In this study, we aimed to investigate the role of ECG-gated 16-detector computed tomography in the detection of coronary artery origination anomalies. Ninehundred and fifty adult patients from January 2005 to June 2006 were evaluated retrospectively. Coronary CT angiography studies had been routinely performed by 16-detector CT scanners with ECG gating. Detector collimation was 16×1 mm, and reconstruction interval 0.5mm. Patients with pre-scan heart rates greater than 75 beats/min were given oral or intravenous beta-blocker. CT scans were obtained with breath hold after intravenous 120 ml iodinated contrast material was given. The coronary CT angiograms were evaluated by thoracic radiologist on Vitrae workstation using axial, multi planar reformation, and three dimensional images. Fourteen coronary artery anomalies were detected in 950 consecutive coronary CT angiographies (1.47%). Identified anomalies were as fallows: origin of right coronary artery (RCA) from left sinus of Valsalva =2, hypoplasia of RCA =2, second left anterior descending artery (LAD) from RCA = 1, origin of circumflex artery (CxA) from right sinus of Valsalva =4, origin of LAD and CxA from 2 different ostia in the left sinus of Valsalva =5. 16-detector CTA can non invasively demonstrate accurate depiction of the origin and course of coronary artery anomalies. It is important to detect coronary artery anomalies because they can be compressed by cardiac chambers and great vessels during their aberrant courses. In addition, coronary CT angiography can be helpful to guide bypass surgery and catheter angiography in these patients.
Koroner Arter Çıkış Anomalilerinin Tespitinde 16 Dedektör Bilgisayarlı Tomografinin Rolü
Keywords: Coronary Angiography; Coronary Artery Anomalies; Coronary CT Angiography; Multi-Detector CT; Multi-Slice CT